The Need for Psychedelic-Assisted Therapy in the Black Community and the Burdens of Its Provision - Smith, Darron T.; Faber, Sonya C.; Buchanan, NiCole T.; Foster, Dale; Green, Lilith (Frontiers in Psychiatry, 2022)
Psychedelic medicine is an emerging field that examines entheogens, psychoactive substances that produce non-ordinary states of consciousness (NOSC). 3,4-methylenedioxymethamphetamine (MDMA) is currently in phase-3 FDA clinical trials in the United States (US) and Canada to treat the symptoms of posttraumatic stress disorder (PTSD). MDMA is used in conjunction with manualized therapy, because of its effectiveness in reducing fear-driven stimuli that contribute to trauma and anxiety symptoms. In 2017, the FDA designated MDMA as a “breakthrough therapy,” signaling that it has advantages in safety, efficacy, and compliance over available medication for the treatment of trauma-, stress-, and anxiety-related disorders such as PTSD. In the US and Canada, historical and contemporary racial mistreatment is frequently experienced by Black people via a variety of macro and micro insults. Such experiences trigger physiological responses of anxiety and fear, which are associated with chronically elevated stress hormone levels (e.g., cortisol and epinephrine), similar to levels documented among those diagnosed with an anxiety disorder. This paper will explore the benefits of entheogens within psychedelic assisted-therapy and their potential benefits in addressing the sequelae of pervasive and frequent negative race-based experiences and promoting healing and thriving among Black, Indigenous and other People of Color (BIPOC). The author(s) discuss the ethical responsibility for providing psychedelic-assisted therapy within a culturally competent provider framework and the importance of psychedelic researchers to recruit and retain BIPOC populations in research and clinical training.